Application of Swamp Wild Plant Extracts as a Source of Botanical Insecticides Against Main Pests of Rice in Tidal Swamp Lands Acid Sulphate - Syaiful Asikin; Eva B E Pangaribuan (Universitas Pattimura, 2022)
Until now, efforts to control plant pests and diseases tend to partner with chemical insecticides. The continuous and unwise use of chemical insecticides will adversely affect the environment and can kill natural enemies, especially parasitoids and predators, cause pest resistance, environmental pollution, and poisoning for pets and users/consumers. To overcome them, it is necessary to find an alternative control that is environmentally friendly, namely by using plant materials as pest and disease controllers, which are called botanical pesticides/insecticides. Plants that have a function as a source of botanical insecticides include swamp wild plants ‘cambai karuk’ (Piper sarmentosum), ‘maya’ (Amarphophallus campanulatus) and ‘sungkai’ (Peronema canescens). It was found FROM this study that the extract of each of the three plant species could be used as ingredients for making botanical insecticides for controlling the main pests of rice (leaf damaging white pest and false white pest) and white rice stem borer in acid sulphate tidal swamp land. The three species of swamp plants could suppress the attack of pests that destroyed rice plants. In rice plants treated with swamp plant extract, the attack rate of leaf damaging pests was 1.65-10.25% and for white rice stem borer, it was 0.95-3.25%. This was lower than those without treatment with an attack rate of leaf damaging pests at 35.25% and rice stem borer at 25.65%. In control with chemical insecticides, the attack rate was 7.92% by leaf damaging pests and 2.45% by stem borers. The application of tested swamp plant extracts was able to significantly reduce dry grain yield loss compared to the control without insecticide/pesticide treatment.